1991
DOI: 10.2527/1991.6993523x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ewe breed and management system on efficiency of lamb production: III. Meat characteristics

Abstract: Effects of management system, ewe breed, sex, and legume grazing on cooking and sensory characteristics and shear force of lamb meat were estimated from data collected on animals produced in three management systems. System 1 lambs were born in late fall and fed to slaughter on a concentrate diet. System 2 lambs were born in January and February and grazed pure stands of alfalfa or ladino clover after weaning. System 3 lambs were born in March and April and remained with their dams on native bluegrass-white cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…Some authors have reported greater values for shear force and toughness of meat from concentrate-fed lambs than from pasture animals (Santos-Silva et al 2002), whereas others did not find significant differences (Notter et al 1991). The results reported for E animals may be related to the relatively greater amount of exercise by kids from E, as suggested by Aalhus et al (1991) for lambs, who found that muscles from exercised lambs were significantly tenderer than muscles from their indoor counterparts.…”
mentioning
confidence: 40%
“…Some authors have reported greater values for shear force and toughness of meat from concentrate-fed lambs than from pasture animals (Santos-Silva et al 2002), whereas others did not find significant differences (Notter et al 1991). The results reported for E animals may be related to the relatively greater amount of exercise by kids from E, as suggested by Aalhus et al (1991) for lambs, who found that muscles from exercised lambs were significantly tenderer than muscles from their indoor counterparts.…”
mentioning
confidence: 40%
“…The ADG of GR+S and DRL-GRE was significantly greater than GR (p b 0.05). Several authors (Ely et al, 1979, Prache et al, 1990Notter et al, 1991;McClure et al, 1994;Zervas et al, 1999) have reported greater ADG in drylot lambs than in grazing lambs, although they worked with weaned heavy lambs raised on different types of pasture, which may determine the degree of gain reduction. In that sense, Joy et al (2007) found that Rasa Aragonesa lambs grazing alfalfa and suckling their dams until slaughter presented similar growth than that observed in drylot lambs, whereas Churra Tensina lambs grazing on mountain pastures and also suckling throughout the raising period showed a lower ADG in relation to those stall-fed .…”
Section: Lamb Performancementioning
confidence: 93%
“…As variações encontradas na maciez são decorrentes de vários fatores, tais como: raça dos animais [21,23,27,30], peso ou idade ao abate [34,39], tipos de músculos [1,42], sistema de manejo [27,28,36] e condições de pré e pós-abate.…”
Section: Efeito Do Peso Ao Abate De Cordeiros Santa Inês E Bergamáciaunclassified
“…Outros autores também não citaram diferenças para FC, tais como: NOTTER, KELLY, BERRY [28] comparando as progênies do cruzamento de ovelhas ½-Suffolk, ½-Rambouillet; ½-Suffolk, ¼-Finnsheep, ¼-Rambouillet ou Dorset com machos Suffolk; e KISHORE, RAWAT, BASUTHAKUR [24] que encontraram em cordeiros machos Dorset x Avikalin e Avikalin médias de FC de 1,75 e1, 86kg, respectivamente.…”
Section: -Força De Cisalhamento (Fc)unclassified